2016
DOI: 10.1038/nutd.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

Liver-specific overexpression of LPCAT3 reduces postprandial hyperglycemia and improves lipoprotein metabolic profile in mice

Abstract: Previous studies have shown that group 1B phospholipase A2-mediated absorption of lysophospholipids inhibits hepatic fatty acid β-oxidation and contributes directly to postprandial hyperglycemia and hyperlipidemia, leading to increased risk of cardiometabolic disease. The current study tested the possibility that increased expression of lysophosphatidylcholine acyltransferase-3 (LPCAT3), an enzyme that converts lysophosphatidylcholine to phosphatidylcholine in the liver, may alleviate the adverse effects of ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Acox1 is the first enzyme of the fatty acid beta-oxidation pathway [35] while Lpcat3 catalyzes the reacylation of lysophospholipids to phospholipids to modulate lysophospholipid availability and metabolism in the liver. It has been shown that LPCAT3 is an important mediator of liver X receptor effects on metabolism [36,37]. The overall results support a strong regulatory role of Bgn in peripheral metabolism.…”
Section: Discussionsupporting
confidence: 60%
“…Acox1 is the first enzyme of the fatty acid beta-oxidation pathway [35] while Lpcat3 catalyzes the reacylation of lysophospholipids to phospholipids to modulate lysophospholipid availability and metabolism in the liver. It has been shown that LPCAT3 is an important mediator of liver X receptor effects on metabolism [36,37]. The overall results support a strong regulatory role of Bgn in peripheral metabolism.…”
Section: Discussionsupporting
confidence: 60%
“…Lysophosphatidylcholine acyltransferase-3 (LPCAT3) preferentially synthesizes unsaturated fatty acid-containing PCs and is induced by liver X receptors (LXRs) and PPARδ in liver 139,140 . Hepatic knockdown of LPCAT3 induces ER stress and inflammation 139 , while its overexpression improves insulin sensitivity and glucose tolerance in wild-type and ob / ob mice 139,141 . Future studies identifying the intracellular signals generated by specific phospholipid species will help clarify their role in insulin sensitivity.…”
Section: Phospholipids and Insulin Sensitivitymentioning
confidence: 99%
“…This is likely caused by the accumulation of lysoPC, which in turn increases microsomal triglyceride transfer protein (MTP) expression and facilitates apoB-containing very low-density lipoprotein (VLDL) assembly and secretion (35). Conversely, mice acutely over-expressing human LPCAT3 in liver for several days show reduced VLDL secretion and lowered hepatic triglyceride levels, perhaps due to the fact that, at reduced levels, lysoPC no longer suppresses fatty acid β-oxidation in hepatocytes (37). These mice also displayed beneficial lipoprotein profiles with increased levels of protective ApoE-rich high-density lipoprotein (HDL) in plasma.…”
Section: Lpcat3 Regulates Very Low-density Lipoprotein Secretionmentioning
confidence: 99%